Classroom Wall Graffiti as a Voice Tool: The Lebanese University as a Case Study - Srour , Ibrahim (Acta Pedagogia Asiana, 2025)
Language carried within it one’s affective notions, psychological struggles, and cognitive abilities. These were expressed through emotions, thoughts, and opinions that reflected one’s social role and status. In this way, language served as a vital tool for communication at the social, institutional, and interpersonal levels. Among its many forms was graffiti. Graffiti represented a form of communication that allowed writers to express their thoughts and feelings freely. This article was based on the premise that classroom wall graffiti played a significant role in voicing the opinions, emotions, and ideologies of their writers. It examined the classroom graffiti written by students at the Lebanese University’s English Department, Faculty of Arts and Humanities. The aim was to highlight the cognitive, behavioral, and interpersonal features of the students’ graffiti in order to demonstrate its effectiveness in expressing their voices. The findings showed that classroom graffiti by these students functioned as a powerful discursive social practice, enabling them to articulate the thoughts and emotions that weighed on their minds.